LIKWIDACJA GMINNEJ SZKOŁY SAMORZĄDOWEJ - WYBRANE PROBLEMY PRAWNE - Czuba-Wąsowska, Magdalena (Zeszyty Prawnicze, 2017)
A Liquidation of a Municipal School. Selected Legal Aspects Summary The main idea of the article concerns legal issues connected with the liquidation process of a school the founding body of which is a local government. This inter alia includes theoretical issues conceming self governing powers of a local government, a subsidiary rule, as well as theoretical and practical aspects of a supervision over a local government. The idea of a school conducted by a local government and its liquidation is explained in detail, including adoption of a resolution on liquidation, notification of an intention to liquidatethe school addressed to the bodies specified by the statute, the opinion of a school supervising authority, as well as adoption of a final resolution on liquidation (in case of obtaining permission from the school supervising authority). The article also covers a number of judicialdecisions, including most recent verdicts on this matter. The article presents conclusions de lege lata and de lege ferenda concerning actions to be undertaken in the process of the liquidation, as well as the duties of a local government body which conducts the school in respect of protecting constitutional rights of the pupils from the liquidated school.